INOVASI STRATEGI PENJUALAN ONLINE DAN SISTEM KEUANGAN DIGITAL PADA UMKM KERUPUK CAK NAN MELALUI PENDEKATAN DESIGN THINKING - Sutrisno; Retno Muslinawati; Elsi Dwi Septiani; Sahra Dwi Irma Rosida (Jurnal Abdi Masyarakat, 2026)
The Cak Nan Crackers MSME in Padangan District, Bojonegoro Regency, has significant economic potential but still faces obstacles in digital marketing and financial management, such as the lack of a brand identity, limited marketplace utilization, and unstructured financial records. This mentoring activity aims to increase the competitiveness of MSMEs through innovative online sales strategies and the implementation of a simple digital financial system with a Design Thinking approach. The mentoring method is carried out in a participatory manner through the stages of empathize, define, ideate, prototype, and test to produce solutions that suit the needs and capacities of partners. The mentoring results show improvements in branding and marketing aspects through the creation of logos, packaging stickers, product photos, and the opening of Shopee and social media accounts, as well as increased partner awareness in maintaining financial records using simple digital applications as a first step towards a more measurable and sustainable business.